Chrozophorin: a new acylated flavone glucoside from Chrozophora tinctoria (Euphorbiaceae) - Delazar,A. (2006)
Preparative reversed-phase HPLC analysis of the methanol extract of the aerial parts of Chrozophora tinctoria (Euphorbiaceae) yielded five flavonoid glycosides, quercetin 3-O-rutinoside (1, rutin), acacetin 7-O-rutinoside (2), apigenin 7-O-b-D-[(6-p-coumaroyl)]-glucopyranoside (3), apigenin 7-O- b-D-glucopyranoside (4) and apigenin 7-O-b-D-[6-(3,4-dihydroxybenzoyl)]-glucopyranoside (named, chrozophorin, 5), the last one being a new natural product. The structures of these compounds were elucidated unambiguously by UV spectroscopic analyses using shift reagents, ESIMS, and 1D and 2D NMR spectroscopic techniques. The free-radical scavenging activity of the methanol extract (RC50 = 2.24 x 10-1 mg/mL) as well as the isolated compounds (1-5) (RC50 = 4.38 x 10-3, 2.26 x 10-2, 7.69 x 10-4, 8.71 x 10-3 and 3.19 x 10-4 mg/mL, respectively) were assessed by the DPPH assay.